PROPER NAMES TRANSLATION TECHNIQUES - Aleshina , O.I. (Scientific practical conference, 2025)
Thisarticleexamines the issues of translatingpropernames. The authorprovidestwoclassifications of translation,describes in detail the specifics of eachtranslationtransformation.Eachindividualtranslationtransformation is illustrated with examples.